2022
DOI: 10.3390/nu14071367
|View full text |Cite
|
Sign up to set email alerts
|

Can Diet Prevent Urological Cancers? An Update on Carotenoids as Chemopreventive Agents

Abstract: Urological cancers, namely prostate, bladder, kidney, testicular, and penile cancers, are common conditions that constitute almost one-quarter of all malignant diseases in men. Urological cancers tend to affect older individuals, and their development is influenced by modifiable metabolic, behavioral, and environmental risk factors. Phytochemicals may have cancer-fighting properties and protect against cancer development, slow its spread, and reduce the risk of cancer deaths in humans. This paper aims to revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…The carotenoid class is well known due to the provitamin A activity of some of its members, primarily the (all-E)-β-carotene, which displays the structural requirements to be bioconverted into two molecules of this indispensable nutrient after consumption. Furthermore, beneficial health effects of the dietary intake of provitamin A and nonprovitamin A carotenoids have been reported and comprise particularly the decreased risk of developing age-related macular degeneration and other eye conditions [22,23], some types of cancer [24,25], and cardiovascular [26,27] and bone diseases [28]. Humans depend on their diet to obtain carotenoids and consequently be exposed to these healthpromoting activities, with the chemical structure of these compounds determining their physicochemical properties; their behaviour through digestion, absorption, metabolism, and distribution; and ultimately, their biological efficacy [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The carotenoid class is well known due to the provitamin A activity of some of its members, primarily the (all-E)-β-carotene, which displays the structural requirements to be bioconverted into two molecules of this indispensable nutrient after consumption. Furthermore, beneficial health effects of the dietary intake of provitamin A and nonprovitamin A carotenoids have been reported and comprise particularly the decreased risk of developing age-related macular degeneration and other eye conditions [22,23], some types of cancer [24,25], and cardiovascular [26,27] and bone diseases [28]. Humans depend on their diet to obtain carotenoids and consequently be exposed to these healthpromoting activities, with the chemical structure of these compounds determining their physicochemical properties; their behaviour through digestion, absorption, metabolism, and distribution; and ultimately, their biological efficacy [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Diet has been explored as a preventive strategy for bladder cancer, with strong evidence only found for arsenic in drinking water [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Limited evidence suggests that a higher consumption of vegetables, fruits, and tea may decrease the risk of bladder cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that making significant lifestyle changes can have an impact on the advancement of low-grade and early-stage prostate cancer [ 4 ]. For example, using 5-alpha reductase inhibitors [ 5 ], consuming green tea catechins [ 6 ], phytoestrogen [ 7 ], and carotenoids [ 8 ] have been found to affect the progression of the disease. Additionally, the intake of certain minerals, particularly zinc, calcium, and selenium, along with high consumption of dietary isoflavones, is recognized as factors that can influence the risk of prostate cancer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%